Immediate Outcome of Mechanically Ventilated Neonate : One Year Experience in Neonatal Intensive Care Unit of Combined Military Hospital Dhaka - Das, Bijoy Kumar; Fatema Begum, Nurun Nahar; Yasmeen, Sabina; Raha, Biplob Kumar (IAHS Medical Journal, 2022)
Background: A large number of neonates in intensive care unit require mechanical ventilation due to various disease conditions. There has been a dramatic fall in neonatal mortality in developed countries with the advent of mechanical ventilation. This study was carried out to see the immediate outcome of neonates who required mechanical ventilation. Materials and methods: This prospective observational study was carried out in Neonatal Intensive Care Unit, CMH Dhaka from January 2016 to December 2016. Neonates who required mechanical ventilation during the study period were enrolled in this study. During the time of mechanical ventilation neonates were followed up for any complication till discharge or death. Results: Total 30 neonates were enrolled in the study. Among them 22(73.3%) of the neonates were preterm and 8(26.7%) were term, 25(83.3%) having birth weight <2500 gm. Respiratory Distress Syndrome was the most common reason for mechanical ventilation accounting for 11(36.7%),other indications were Perinatal Asphyxia 7(23.3%), Septicemia 6(20.0%), Congenital Pneumonia 5(16.7%) and Meconium Aspiration Syndrome 1(3.3%). Common complications during the period of ventilation were Septicemia (40.0%), Acute Renal Failure (16.7%), Pneumonia (16.7%), Pulmonary Hemorrhage (10.0%), Intraventricular Hemorrhage (6.7%), Pneumothorax(10.0%) and Heart Failure (6.7%). 17(56.7%) neonates survived and 13(43.3%) were died. Most of the neonate died of Perinatal Asphyxia 4(57.1%), Septicemia 3(50.0%), RDS 5(45.5%) and Congenital Pneumonia 1(20.0%). Conclusion: The survival rate of ventilated neonates was 56.7%. The higher gestational age and birth weight was significantly associated with better outcome. Septicemia and Pneumonia (PNA) was the leading cause of death in this study. Effective measures for prevention and management of sepsis could improve the outcome of neonates in NICU. IAHS Medical Journal Vol 4(1), June 2021; 27-32